I Igniting Lerning: How Leadership and Teaching Prowess Transform Primary Schools in Pedurungan, Semarang - Afina Sulistyahati; Kusumaningsih, W; Nurkolis (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
The quality of primary education is a fundamental determinant of individual life trajectories and national development. This research aims to analyze the partial and simultaneous impact of principals’ instructional leadership and teachers’ pedagogical competence on learning quality of elementary schools in Kecamatan Pedurungan of Semarang. Employing a quantitative, explanatory research design, the study involved 389 elementary school teachers, from whom a sample of 197 was designated using the Slovin formula and proportional random sampling. Data were collected via questionnaires and analyzed using multiple linear regression. The findings reveal that principals’ instructional leadership and teachers’ pedagogical competence significantly affect learning quality of elementary schools, both partially and simultaneously. The robust correlation, quantified at 77.9%, between the synergistic influence of instructional leadership and pedagogical competence on learning quality carries profound implications for educational practice and policy. Effective instructional leadership transcends mere administrative oversight; it encompasses the proactive engagement of school leaders in curriculum development, instructional supervision, and the professional growth of educators. Concurrently, pedagogical competence refers to an educator’s proficiency in planning, executing, and evaluating instruction